Clinical impact of atrophic changes in remnant pancreas on the development of nonalcoholic fatty liver disease after pancreaticoduodenectomy. Issue 4 (12th February 2022) - Yamamura, Kensuke; Yamashita, Yo‐ichi; Yamao, Takanobu; Kitano, Yuki; Arima, Kota; Miyata, Tatsunori; Higashi, Takaaki; Hayashi, Hiromitsu; Beppu, Toru; Baba, Hideo
Abstract: Aim: The aim of this study was to evaluate risk factors for nonalcoholic fatty liver disease (NAFLD) after pancreaticoduodenectomy (PD), with a special focus on remnant pancreatic volume (RPV) as assessed using computed tomography (CT). Methods: From February 2004 to June 2017, 101 patients who underwent PD in our institution were enrolled. We defined a CT attenuation value of less than 40 HU as hepatic steatosis and measured RPV at 7 days, 3 months, and 1 year after PD using the SYNAPSE VINCENT system. The incidence of NAFLD and RPV were compared between the two groups according to reconstruction with pancreaticogastrostomy (PG) or pancreaticojejunostomy (PJ). Results: The incidence of NAFLD at 3 months after PD was 39.6% (40/101). The RPV ratio (RPV at 3 months or 1 year divided by RPV at 7 days after PD) at both 3 months and 1 year was significantly smaller in the PG group than in the PJ group (59% vs 73%, P < .001 and 53% vs 67% P < .01, respectively). A positive correlation between the RPV ratio and liver CT value at 3 months was found. The multivariate analysis identified three independent risk factors for NAFLD: female sex (odds ratio [OR] 8.16, 95% confidence interval [95% CI] 2.27‐35.9, P < .001), PG reconstruction (OR 3.87, 95% CI 1.04‐15.6, P = .04), and RPV ratio ≤60% (OR 3.44, 95% CI 1.06‐11.8, P = .001). Conclusion: Atrophic change in the remnant pancreas is significantly associated with the development of NAFLD, and PJ reconstruction may be superior to PG from the viewpoint of NAFLD development. Abstract : Correlation analysis of RPV, RPV ratio, and liver attenuation value. RPV ratio, but not RPV, was positively correlated with the liver attenuation value.